The Integrated Effect of Both Methodism and Pheromone Traps in Reducing the Population Density of White Flies - Mohsin, Alyaa K. (Journal of Science in Medicine and Life, 2025)
The findings suggest that whitefly populations can be controlled through the use of pheromone traps which in turn helps to improve crop health and yields— by reducing chemical pesticide application. It also calls for more sustainable pest management practices, underscoring the significant place of agriculture in the economy in the long run. Integrating pheromone traps into Methodism might be a potential control measure against whitefly populations. The act would promote the growth of crops and decrease dependency on chemical pesticides, based on this discovery. The research underscores the value of incorporating sustainable pest management practices that can help agriculture down the road for its own good.